2001
DOI: 10.1007/s002310000148
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer distribution in rectangular ducts with V-shaped ribs

Abstract: Heat transfer distributions are presented for a rectangular duct with two opposite wide walls arranged with V-shaped ribs pointing upstream or downstream relative to the main¯ow direction. The rectangular duct has an aspect ratio of 1/8. The parallel V-shaped circular ribs are arranged staggered on the two wide walls. The rib height-to-hydraulic diameter ratio is 0.06, with an attack angle of 60°. The pitch-to-height ratio equals 10. The tested Reynolds numbers range from 1000 to 6000. The test surface is spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5] The secondary flow originated by rib inclination interacts with main flow ensuing higher turbulence and heat dissipation. Taslim et al 4 observed that V-rib produces twin secondary flow cells progressing along the V limbs result in notable enhancement in heat transfer over inclined rib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] The secondary flow originated by rib inclination interacts with main flow ensuing higher turbulence and heat dissipation. Taslim et al 4 observed that V-rib produces twin secondary flow cells progressing along the V limbs result in notable enhancement in heat transfer over inclined rib.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of V-rib on heat and fluid flow has been experimentally investigated by several investigators for different geometrical parameters of roughness and duct aspect ratios. [4][5][6][7][8][9][10][11][12][13][14] Many investigators 4,5,13 reported that V-rib pointing in the flow direction attains higher rates of heat flow than apex facing upstream for the range of Reynolds number normally used in solar air heaters. Tanda 15 explored that the thermo-hydraulic performance of duct flow could be considerably improved by discrete roughness elements.…”
Section: Introductionmentioning
confidence: 99%
“…Various other studies show that the use of V-ribs with different orientation and positions enhances the heat transfer and boost up the performance of a solar air heater as well as other applications. (Han and Zhang, [10]; Lau et al, [11,12]; Han et al, [13,14]; Taslim and Spring, [15]; Taslim et al, [16]; Wang and Sunden [17]; Wright et al, [18]; Olsson and Sunden, [19]; Gao and Sunden, [20,21]; Jia et al, [22,23].…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the 45-deg angled V-shaped ribs produced the higher heat transfer performance compared with other rib configurations. Gao and Sunden (2001) measured the heat transfer coefficients between adjacent pairs of 60-deg V-shaped ribs. The results showed that the local Nusselt number around the middle point between a pair of adjacent ribs was higher than that near the ribs in the main flow direction.…”
Section: Introductionmentioning
confidence: 99%